Aqueous and organic extract of PM2.5 collected in different seasons and cities of Japan differently affect respiratory and immune systems. (April 2018) - Chowdhury, Pratiti Home; Okano, Hitoshi; Honda, Akiko; Kudou, Hitomi; Kitamura, Gaku; Ito, Sho; Ueda, Kayo; Takano, Hirohisa
Abstract: Particulate matter with diameters <2.5 μm (i.e., PM2.5 ) has multiple natural and anthropological sources. The association between PM2.5 and the exacerbation of respiratory allergy and asthma has been well studied, but the components of PM2.5 that are responsible for allergies have not yet been determined. Here, we elucidated the effects of aqueous and organic extract of PM2.5 collected during four seasons in November 2014–December 2015 in two cities (Kawasaki, an industrial area and Fukuoka, an urban area affected by transboundary pollution matter) of Japan on respiratory health. Ambient PM2.5 was collected by high-volume air samplers and extracted into water soluble and lipid soluble components. Human airway epithelial cells, murine bone marrow-derived antigen-presenting cells (APC) and splenocytes were exposed to PM2.5 extracts. We measured the cell viability and release of interleukin (IL)-6 and IL-8 from airway epithelial cells, the DEC205 and CD86 expressions on APCs and cell proliferation, and TCR and CD19 expression on splenocytes. The water-soluble or aqueous extracts, especially those from Kawasaki in fall, had a greater cytotoxic effect than the lipid-soluble or organic extracts in airway epithelial cells, but they caused almost no pro-inflammatory response. Extract of fall, especially the aqueous extract from Fukuoka, increased the DEC205 and CD86 expressions on APC. Moreover, aqueous extracts of fall, summer, and spring from Fukuoka significantly increased proliferation of splenocytes. Organic extract of spring and summer from Kawasaki significantly elevated the TCR expression, and organic extract of summer from Kawasaki decreased the CD19 expression. These results suggest that PM2.5 extract samples are responsible for cytotoxicity in airway epithelial cells and for activating APCs and T-cells, which can contribute to the exacerbation of respiratory diseases such as asthma. These effects can differ by PM2.5 components, collection areas and seasons. Graphical abstract: Image 1 Highlights: Cytotoxic and inflammatory potential found in aqueous and organic extracts of PM2.5 . Seasonal and location variations changed PM2.5 components in two cities in Japan. Correlation was established between heavy metals and cytotoxicity of airway cells. PM2.5 extracts activated APCs and T cells, which are responsible for allergy. Abstract : Respiratory health effects of PM2.5 extracts depend on their components.